Diffuse Adenomatosis and Hepatocellular Carcinoma Treated with Liver Transplantation in an Adolescent Female with Kabuki Syndrome with a Novel KMT2D Gene Mutation - Leander D. Timothy; Heidi D. Lehrke; Vishal S. Chandan; Amy B. Kolbe; Katryn N. Furuya (Hindawi Limited, 2019)
Kabuki syndrome (KS) is a rare disorder primarily associated with mutations in the KMT2D and KDM6A genes. Several tumors have been reported with KS; however, there have been no reports of hepatocellular carcinoma (HCC) or hepatic adenomatosis. We present an adolescent girl with KS and a novel KMT2D mutation who developed diffuse adenomatosis, HCC, and subsequently underwent liver transplantation.